Resistir e Re-existir na Epidemia: Um estudo com as mulheres cuidadoras de crianças com síndrome congênita do Zika no interior da Paraíba - Cabral, Martha Ysis Ribeiro (2019)
In April 2015, the Zika virus occurrence in Brazil had confirmation; this fact had treated as something of less offensive potential when compared to Dengue, an old acquaintance of Brazilians. In the second semester of that same year, the link between the agent and the increase on the microcephaly cases in the northeast of the country had confirmation. The Zika epidemic, so the malformations cases, had narrated from the most diverse speeches. The aim of this work was compare the speech of the Brazilian government about this event with the narrative of women who are caregivers of children born with Zika congenital syndrome, which had been attending by an outpatient clinic located in Campina Grande-PB and to draw a sociodemographic profile of the users. Thus, we consult official documents, such as protocols, resolutions, laws and decrees to verify the construction of the content so as the form of the official hegemonic narrative about the fact. We also carried out a bibliographic research, which the results we used for the theoretical foundation of the present work with the intent of better understand the biopolitics exercise on a vulnerable population in the previous periods and during the outbreak. For this, we analyzed works of Michel de Foucault and to better contextualize the described facts we used texts of Debora Diniz, who is reference on discussions about the Zika arrival and consequences for the social context. To investigate the gender issues pertaining to the data, we used the Judith Butler production. In order to approach at the women's narrative we conducted a field survey through interviews, which consisted in a semi-structured instrument separated into topics and divided by themes such as daily routine, social context and access to public services and policies. With the obtained data was possible reach the caregivers sociodemographic profiles and also allowed us to collect reports from their lived experience. As a result, we verified the initial hypothesis that women who living in areas where the epidemic had a greatest impact were already in a precarious condition, which was aggravated after the congenital malformations outbreak caused by zika virus infection during pregnancy. This situation led the most part of the women to assume the position of caregivers. We also verified the ineffective performance of the Brazilian government in reaction to the epidemic.